Larvicidal activity of lemon oil and lemon crude extract against Spodoptera litura - Rahim, Naufal Fahmi (2018)
Plant essential oil play important role as one of the biopesticide in controlling insect pest. Lemon oil extract have the potential to be used as biopesticide to against insect pest of cruciferous crop. Larvae of Spodoptera litura are known to cause enormous losses to many important cultivated crops. Thus the objective of this study is to evaluate the larvicidal activity of lemon extract against S. litura. Experiment was conducted at Toxicology laboratory, Department of Plant Protection Faculty of Agriculture, UPM Serdang. Larvicidal activity of S.litura larvae was determined using leaf dipping method and feeding deterrence index. The larvae mortality, leaf area and dry weight of feaces were recorded at 24, 48, 72 and 96 hours after treatment. The treatment concentration for both lemon crude extract (LCE) and lemon oil extract (LOE) were 0.01%, 0.05%, 0.1%, 1%, 2%, Spinosad as the positive control and negative control was distilled water. The mortality data was subjected to Probit Analysis to determine the toxicity level by the LC50 value. Results showed that LC50 value at 96 hours exposure was 237.958 ml/L for lemon crude extract and lemon oil extract was 496.412 ml/L. The antifeedant showed the rate increases when the concentration and exposure time increased. All concentration gave 100% antifeedant rate at 96 hours. The lowest antifeedant was 1.87% at 0.01% LOE at 24 hours. LCE and LOE showed positive result for controlling S.litura as well as environmental friendly.